The optimisation and evaluation of public health literacy - Sawyers, Luke (2024)
Introduction: Health Literacy (HL) is a key skill for the prevention of adverse health and the maintenance and promotion of good health outcomes, and is generally agreed to reflect a person’s ability to understand, access, appraise and apply health information. Due to HL reflecting a person’s skill to navigate health information, public HL has become a high priority in recent times. This growth has, however, expanded in parallel with disputes – and varied interpretations - regarding its conceptualisation. This heterogeneity may therefore lead to reliability, validity, and comparability issues. Moreover, many HL models are formed in reference to adults, and do not include differences in children compared with adults. Children actively engage in health decisions, and understanding potential HL differences is thus essential for supporting the transition towards health autonomy. Clarity on child and adult HL measurement appears unmet currently, and minimal child HL assessments have been conducted across England. Aims: Two aims were outlined: to investigate the conceptual nature of HL in community adult and child populations; and to gather preliminary data on the state of child HL in England.